Wi-Fi Telephony : - Chandra, Praphul (Elsevier/Newnes, 2007)
This book will be among the first to discuss Session Initiation Protocol (SIP), Quality of Service (QoS), and interoperability in connection with Wi-Fi telephony. Security challenges are also presented and solved along these malleable wireless boundaries. In short, this book provides all the information necessary for effective, reliable, crystal clear Wi-Fi telephony service and implementation.